When Pigasso met Mootisse - Laden, Nina (Chronicle Books, 1998)
Pigasso, a talented pig, and Mootisse, an artistic bull, live across the road from one another, but when conflicts arise they build fences that ultimately become modern art masterpieces. Includes biographies of the real-life artists, Henri Matisse and Pablo Picasso.